2007
DOI: 10.1080/10739140601000616
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Evaluation of a Low Cost Interface for the Determination of Elemental Speciation by Gas Chromatography Coupled to Inductively Coupled Plasma Mass Spectrometry (GC‐ICP‐MS)

Abstract: The construction and evaluation of a low cost, easily demountable interface to couple capillary gas chromatography to inductively coupled plasma mass spectrometry detection is described. Using this interface, the capillary column can be maintained at a high temperature through to the tip of the torch injector using a transfer line heated by a combination of hot argon and electrical resistance. The interface is suitable for analytes with boiling points up to 2308C, allowing for the analysis of low and high boil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The actual union of the gas chromatographic column with the ICP torch has undergone several improvements since its inception and a brief but well-written history is detailed by Watts et al 2 Primarily, the issue with this coupling has been the necessity of maintaining the column temperature once it left the oven for insertion into the torch. However, this issue, which was once prohibitive in the analysis of very high molecular weight, yet volatile compounds, is usually no longer problematic, although Aguilar-Martınez and coworkers recently reported that they could not analyze for triphenyltin when using a PTFE tube (80 cm long and 1.5 mm i.d.)…”
Section: Technical Innovationsmentioning
confidence: 99%
“…The actual union of the gas chromatographic column with the ICP torch has undergone several improvements since its inception and a brief but well-written history is detailed by Watts et al 2 Primarily, the issue with this coupling has been the necessity of maintaining the column temperature once it left the oven for insertion into the torch. However, this issue, which was once prohibitive in the analysis of very high molecular weight, yet volatile compounds, is usually no longer problematic, although Aguilar-Martınez and coworkers recently reported that they could not analyze for triphenyltin when using a PTFE tube (80 cm long and 1.5 mm i.d.)…”
Section: Technical Innovationsmentioning
confidence: 99%
“…The nebulisation and transport efficiency of the CE-ICP interface was approximated at 10%, about an order of magnitude more efficient than conventional ICP-AES sample introduction. The CE-ICP-AES method separated standard solutions of Ba 2+ and Mg 2+ within 30 s. Finally, a low cost and easily demountable interface to couple capillary GC to ICP-MS maintained the capillary column at a high temperature through to the tip of the torch injector using a transfer line heated by a combination of hot Ar and electrical resistance (Watts et al 2007). The design and construction of the interface were described in detail, and the interface was found to be suitable for analytes with boiling points up to 230 °C.…”
Section: Hyphenated Speciation Techniquesmentioning
confidence: 99%